Analisis Pengaruh Mutu Pelayanan IGD Terhadap Kepuasan Pasien Di RUMKIT TK II Iskandar Muda Banda Aceh - Muhammad Ilham Syufi; Juliandi Harahap; Deli Theo (Pusat riset dan Inovasi Nasional, 2024)
It can be said that patient satisfaction is an abstract thing and the results vary greatly because basically it really depends on each individual's perception. Patient satisfaction can be said to be fulfilled if the services provided are in accordance with their expectations. The aim of the research is to analyze the Quality of Emergency Room Services on Patient Satisfaction at RUMKIT TK II Iskandar Muda Banda Aceh. The research design used in this research is an analytical survey with a cross sectional design. The population in this study was all 2,058 emergency room patients. The number of samples to be studied is 95 people. Data analysis was carried out using univariate, bivariate and multivariate analysis. The statistical tests used are the chi square test and logistic regression. The results of the chi square test research show that there is an influence of 5 variables, namely reliability, responsiveness, assurance, empathy and physical evidence, which have a p-value <α 0.05, meaning that reliability, responsiveness, assurance, empathy and physical evidence influence patient satisfaction in the RUMKIT TK ER. II Iskandar Muda Banda Aceh and the multivariate test shows that the 5 variables of reliability, responsiveness, assurance, empathy and physical evidence influence the results of the multiple logistic regression test showing that the responsiveness variable is the most dominant with an odds ratio (OR) of 15,104, meaning 15 times influencing patient satisfaction. The conclusion was that the dominant responsiveness variable had the most influence on patient satisfaction at the RUMKIT TK II Iskandar Muda Banda Aceh emergency room. It is recommended for hospitals to adopt policies to increase patient responsiveness in the ER in order to produce optimal patient satisfaction.